2023
DOI: 10.26599/nre.2023.9120068
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of catalysts for ammonia synthesis

Abstract: Ammonia plays a crucial role in agriculture and chemical engineering, and acts as a promising carbon-free transportation fuel. Catalysts design is deemed as a key to solve the restriction of energy-intensive Haber-Bosch process of ammonia production. With the development of computational modeling, computation-aided catalyst design serves as one important driving force for material innovation, saving a lot of experimental efforts based on trial and error. Computational modeling not only provides fundamental mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…DFT calculations were performed to investigate the origin of the activity of the Sb SA/N-Ti 3 C 2 T x catalyst toward NRR. Herein, the Ti 3 C 2 O 2 structure model was constructed as a substitute for Ti 3 C 2 T x . First, the oxygen vacancy formation energies on Ti 3 C 2 O 2 , N-Ti 3 C 2 O 2 , and Sb SA/N-Ti 3 C 2 O 2 were calculated because the abundant oxygen vacancies could promote the exposure of metal active sites.…”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations were performed to investigate the origin of the activity of the Sb SA/N-Ti 3 C 2 T x catalyst toward NRR. Herein, the Ti 3 C 2 O 2 structure model was constructed as a substitute for Ti 3 C 2 T x . First, the oxygen vacancy formation energies on Ti 3 C 2 O 2 , N-Ti 3 C 2 O 2 , and Sb SA/N-Ti 3 C 2 O 2 were calculated because the abundant oxygen vacancies could promote the exposure of metal active sites.…”
Section: Resultsmentioning
confidence: 99%
“…A well-designed electrocatalyst can boost the activity and selectivity of the NitRR. 139,169 We hope this review helps researchers to develop new catalyst strategies to realize green ammonia electrosynthesis from nitrate under mild conditions. In addition, outstanding electrocatalysts are encouraged to promote the nitrate electroreduction technology from the laboratory to industry, thereby managing nitrate-rich wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Alloying Au with another transition metal to form a bimetallic structure is a promising strategy, which not only can tailor the adsorption energy of nitrogen species on metals but also can reduce the catalyst cost. [18][19][20][21] Cu has been widely developed as a promising dopant to improve the NRR performance through morphological modification and electronic reconstruction. [22][23][24][25] It has been reported that PdCu nanoparticles anchored to boron nanosheets (PdCu/B) showed superior NRR performance compared to their monometallic counterparts because the introduction of copper can form symmetry-breaking interfacial structures and change the adsorption conformation of N 2 , thus optimizing the NRR performance.…”
Section: Introductionmentioning
confidence: 99%